COVID-19, 5G conspiracies and infrastructural futures. (November 2020) - Meese, James; Frith, Jordan; Wilken, Rowan
This article examines the emergence of conspiracy theories linking COVID-19 with 5G, with a focus on Australia, the United States and United Kingdom. The article is in two parts. The first details long-standing concerns around mobile technologies and infrastructures before showing how they translate to specific worries about 5G technology. The second shows how these fears have fuelled specific conspiracies connecting 5G with COVID-19, how they have animated protests and acts of vandalism that have occurred during the pandemic, and the ongoing engagement of conspiracists with official inquiries into 5G. Finally, we argue that a productive way to understand what is happening with 5G is to look beyond conspiracy theories to a larger set of concerns. We argue that the battle for control of 5G infrastructure can be productively understood in geopolitical terms, as forms of economic statecraft, which partly explains why governments are increasingly concerned about countering misinformation and disinformation around 5G.